Efficiency and Ropiness of Traditional White and Ultrafilteration Cheese as Affected by Psycrotroph Bacteria - ALLAH MIRZAEI†, H.; EZZATI, R.; DEZYANI*, M. (Asian Journal of Chemistry, 2009)
During cheese ripening, some of water insoluble casein change towater soluble nitrogen which include intermediate hydrolyzate proteinand free amino acids. In this work, ripening and efficiency of traditionalwhite cheese and ultrafilteration cheese as affected by Psycrotroph bacteriawas investigated. The result showed that amount of Psycrotroph bacteriaon the white and ultrafilteration cheese was significant. Also, there wasa good correlation between Psycrotroph bacteria and ratio of solublenitrogen to total nitrogen during ripening period. In fact, as thePsycrotroph bacteria increase, the ratio of soluble nitrogen to total nitrogenincreased during ripening period. The per cent of N recovery (efficiencyindex) for ultrafilteration and traditional white cheese was 88.01-90.45and 77.23-80.52, respectively. The effect of changing above parameteron ultrafilteration cheese is more than white cheese.